What Kind of Commitment Does a Final-Earnings Pension Plan Elicit? - Luchak, Andrew; Gellatly, Ian (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2001)
SummaryIn a sample of 427 employees in a large, unionized public utility company, we examined the incentive effects of a final-earnings pension plan on employees’ commitment to the organization. Two types of organizational commitment, affective and continuance commitment were measured using scales described by Meyer and Allen (1997). We found evidence that higher accruals under the pension plan increased continuance commitment but reduced affective commitment. Organizational commitment was also found to vary by job satisfaction, specific training, seniority, wage premia, and the perceived effectiveness of alternative dispute resolution methods. Implications for pension theory, research, and policy are discussed.